MESANE KANSERİ TANISINDA SERUM CA 19-9 VE CA 125 DÜZEYLERİNİN ROLÜ - HAMELİ, Hüseyin and ÖZKAN, Burak and ERÖZENCİ, Ahmet and SOLOK, Vural (Cerrahpaşa Medical Journal, 2019)
Background and design.- A non-invasive marker test for bladder carcinoma would not only decrease the cost, but also improve patient quality of life. For bladder carcinoma, tumor growth or invasion associated molecules may serve as markers and they may be detected non-invasively. Carbonhydrate antigen (CA) 19-9 and 125 are useful tumor markers for human cancer, especially in gastrointestinal and gynecologic malignencies. In this study, our aim is to determine the efficiancy of serum CA 19-9 and 125 levels for the detection of bladder carcinoma different from other studies. For this purpose, serum samples were obtained from 49 patients with bladder carcinoma and from 24 patients with benign prostate hyperplasia and 23 patients with nephrolithiasis. Approximately 2 ml serum sample was obtained and aliquated for electro-chemiluminesence immunoassay. Results.- CA 19-9 was determined as positive for 6 patients in bladder carcinoma group. It was positive for 1 patient in the benign prostate hyperplasia and for 4 patients in the nephrolithiasis group (p > 0.05). CA 125 was determined as positive for only one patient in the bladder carcinoma group. 4 patients in the nephrolithiasis group had positive CA 125 level (p > 0.05). The overall sensitivity and specifity were % 12.2 and % 89.4 for CA 19-9. CA 125 has % 2 sensitivity and %91.5 specificity for bladder carcinoma. Conclusion.- In the population tested, serum CA 19-9 and CA 125 determined as not effective in the diagnosis of bladder carcinoma with regard to the sensitivity and specifity values and they could not offer more sensitivity than the other tumor markers and/or cytology for bladder carcinoma.